Comparative evaluation of serum ANA, anti-DNA, RF and SMA antibodies in oral lichen planus and contact and drug lichenoid reactions - Ali Reza Granmayeh; Parichehr Ghalyani (Isfahan University of Medical Sciences, 2011)
Introduction: Oral lichenoid reactions (OLR) are disorders which cannot be distinguished from oral lichen planus (OLP) by their clinical or histopathological features. In recent years both disorders have been considered T-cell mediated inflammatory diseases. The aim of this study was to gather more information to help better distinguish these two lesions.Method and Materials: In this descriptive-analytical study, blood samples were taken from 80 patients (59 females and 29 males) and sent to the laboratory for histopathological diagnosis based on WHO criteria. After separating the blood sera of the samples, the sera were evaluated by ELISA for the presence of ANA, anti-DNA, RF, and SMA auto-antibodies. Data was analyzed with SPSS using the chi-squared test and t-test (α = 0.05).Results: The mean ages were 48.62 and 49.38 for OLP and OLR patients, respectively. There were no significant differences in ANA and RF blood levels (p value > 0.05). Anti-DNA and SMA antibodies were not detected in the blood samples. No significant differences were noted in the blood levels of these antibodies (p value > 0.05).Conclusion: According to the results of the present study, no significant differences were observed between the OLP and OLR patients in relation to the presence or absence of ANA, anti-DNA, RF, and SMA auto-antibodies in the blood samples. Key words: Auto-antibodies, Autoimmune disease, Oral lichen planus, Oral lichenoid reaction